(untitled) (Studia Prawnicze / The Legal Studies, 1985)
If it is impossible to use the term “deontic logic” to denote logic of norms, a philosopher of law, while asking himself a question why legal norms given in our experience are binding, does not know which logical (discursive) means justify the binding force of legal secondary norms. Meaning, and for philosophy of law meaning consisting in providing for logic grounds for conclusion within “extension” of legal norms and conclusions connected with complementing of those norms, belongs, first of all, to deontic logic as logic of norms and to deontic logic as logic on deontic statements only in the second place and after it has been assumed that logic on deontic statements is only added to logic of norms. Normative deductive conclusions (in the above mentioned meaning) exist and are undeniable. Thus, those who think that logic of norms is impossible are wrong. The importance of such logic of norms consists in the fact that the philosopher of law knows, owing to it, what - from a logical point of view - explains binding force of secondary norms.